Menginvestigasi Hubungan antara Citra Kuliner, Restoran, dan Kegiatan Kuliner terhadap Keinginan Berkunjung Ke Kawasan Petak Sembilan - Dewantara, Yudhiet Fajar; Pramanik, Purwanti Dyah; Anom, Rahmat Indra Pratama; Arafah, Willy; Ingkadijaya, Rahmat (Jurnal Ilmiah Pariwisata, 2023)
The food tourism image, which includes the notion of food, huts, and food activity, is formed by visitors’ perceptions through their experiences. The study aimed to investigate the correlation of food image, huts image, and food activity culinary partially on visitors’ willingness to visit Kawasan Petak Sembilan (KPS) Glodok West Jakarta. Ninety respondents were employed, which were chosen by purposive sampling. The data was analyzed by SMART-PLS. The study reported that huts and food activity images partially correlated positively and significantly with visitors’ willingness to visit. However, the food image didn’t link to visitors’ desire to see it. The KPS is suggested to promote authenticity, inherent to the uniqueness of a destination’s culture and Buddhist temple cuisine. In contrast, many visitors visit KPS for worship in the temple. Keywords: Food Tourism Image, Gastronomy, Intention To Visit, Visitors